Legal Analysis of Legal Protection for Children as Victims of Incest Criminal Act - Faisal; Muhdar, Gamar; Weku, Robert Lengkong; Budiono, Arief (Dinasti Research, 2025)
Background: In society, children have a highly vulnerable position, as their physical and mental condition is not yet strong and mature. There have lately been many cases of crimes against morality which involve children, especially the crime of sexual violence, including incest. Objective: This paper aims to analyze: (1) the law on child victims of incest applied at the Ternate City Police Force and (2) the obstacles in applying the law to protect child victims of incest at the Ternate City Police Force. Methods: This research was classic doctrinal research which employed a statute approach and a library approach. To collect data in this study, the researchers employed literature and legislation studies. Results: It was found that efforts provided for victims of underage sexual intercourse and rape in the criminal justice system are implemented through preventive and repressive approaches carried out by both the community and the government. Perpetrators of incest rape are charged with 3 legal regulations, namely the Sexual Violence Crime Law, the Criminal Code, and the Child Protection Law. The existing obstacle is that not many people understand the process of handling incest cases which should be punished more severely than ordinary rape.